Optimal Use of L1 and L2 in Teaching Chinese to Sri Lankan Students: Approaches and Challenges - Noel Dassanayake (Indonesia Approach Education, 2021)
Traditional perspectives on monolingual education and total immersion have been substituted by more novel approaches to multilingual education such as translanguaging and partial immersion where the learners’ language repertoire is paid adequate respect. The present study investigates the role of L1 and L2 in teaching Chinese in Sri Lanka using 42 adult Chinese language learners in Sri Lanka as informants and a structured questionnaire was used as the main data collection tool. The informants have a highly divided perspective towards the use of L1 and L2 in the classroom. Most students have favored English instruction considering its efficacy in career prospects and Sinhala for convenience of comprehension. Considering the existing situation of Chinese language textbooks, language policy, and recent trends in multilingualism in Sri Lanka, total immersion is less likely to bring optimal effectiveness in teaching Chinese. The present study suggests that partial immersion and translanguaging would be more constructive for Sri Lankan students if cautiously handled with less hindrance to the delivery of target language content and its accuracy. A multilingual approach would, on one hand, offer a safe space for students to communicate while penetrating cross-cultural barriers through cultivation of culture-sensitivity.